Fabrication of nano composite hydrogels based on polyvinyl alcohol for biomedical applications / Ali Karimi - Ali, Karimi (2016)
In order to obtain nontoxic, tissue-compatible and efficient hydrogels for biomedical applications, Polyvinyl alcohol (PVA) / Na+-montmorillonite (Na+-MMT) nanocomposite hydrogels were prepared by a cyclic freeze-thaw process (physical method). Effect of nanoclay content and sonication mixing on the nanocomposite structure and morphology as well as its properties (mechanical, thermal), and also its swelling and deswelling kinetics were investigated. Glutaraldehyde reacts with PVA to form covalently cross-linked networks. The acetal linkages were formed between hydroxyl groups of PVA and aldehyde groups of glutaraldehyde that was used for physicochemical synthesis of nanocomposites. A novel PVA nanocomposite hydrogel was synthesized by physicochemical method. Effect of physical and physicochemical cross linking on the structure, morphology, thermal, mechanical, swelling and deswelling properties of nanocomposite hydrogels were investigated and were compared together. The results were shown that physicochemical crosslinking of PVA nanocomposite leads to decreasing of crystallinity and melting temperature also increasing the Hardness and Water vapor transmission rate (WVTR) values than physical crosslinked. Swelling and deswelling measurements were done by gravimetric method and indicated that controlled crosslinking of PVA nanocomposite hydrogel caused to increase the swelling ratio and also decrease the cumulative amount of water loss. Sorption and desorption kinetics for both physical and physicochemical methods were based on diffusion mechanism and obey the Fickian model. As an important result using the controlled crosslinking can obtain the PVA nanocomposite hydrogel with higher swelling capacity than conventional PVA nanocomposite hydrogel. In order to find an optimum amount of nanoclay content for achieving the optimal Equilibrium water content (EWC) and WVTR properties of nanocomposite cryogels, my investigations were performed on the barrier and swelling properties of the nanocomposites and it was shown that Na+-MMT may act as a co-crosslinker. According to the results, the swelling characteristics of nanocomposite cryogels increases with the nanoclay content up to 1-2% nanoclay, after that they start to decrease uniformly. In contrast, the water removal from cryogels decreased and its time of removal prolonged on increasing the nanoclay content. Based on the results of WVTR measurements, the barrier properties of the nanocomposites can be improved by increasing the nanoclay content and it is concluded that the optimum range of nanoclay for having optimum WVTR at 37 °C is up to 1% nanoclay. It was found that the EWC of PVA nanocomposite cryogel containing 1% nanoclay, having 74% water content compared to the other nanocomposites at 37 °C. Results of EWC (above 60%) and WVTR (at about 8.5 g/m2/h) are within the acceptable range for biomedical applications such as skin treatment and wound dressing. With the aim of investigation on the antibacterial properties of PVA/Na+-MMT nanocomposite hydrogels against two types of bacteria, Escherichia coli (E-Coli); as a gram negative bacteria and Staphylococcus aureus (S-Aureus); as a gram positive bacteria, polyvinyl pyrrolidone – Iodine (PVP-Iodine) has been used in the hydrogel network. The effect of nanoclay content on release of antibacterial agent for loaded hydrogels was also investigated in vitro and found to be dependent on crosslinking amount due to interaction between PVA and nanoclay.